Women and Knowledge in Early Christianity - Tervahauta, Ulla; Miroshnikov, Ivan; Lehtipuu, Outi; Dunderberg, Ismo (Vigiliae Christianae, Supplements, 2017)
Women and Knowledge in Early Christianity offers a collection of essays that deal with perceptions of wisdom, femaleness, and their interconnections in a wide range of ancient sources, including papyri, Nag Hammadi documents, heresiological accounts and monastic literature. Readership: Scholars of early Christianity, ancient history and philosophy and anyone interested in questions pertaining to how gender and the role of women were perceived in late Antiquity.